Irony and Parody in Jacqueline Woodson’s Harbor Me: A Postmodernism Study - Aulina, Winda; Hanifa, Siti (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
This study concerns to discuss the Irony and Parody in Jacqueline Woodson’s novel entitled Harbor Me. This study is focused on postmodern theory, since the novel tells about social phenomena in daily life such as irony and parody. This study aims to disclose how irony and parody are reflected in Harbor Me novel by Jacqueline Woodson.This study was conducted by applying a qualitative type since the data are in the form of words. The source of data in this study is Harbor Me novel by Jacqueline Woodson. The data are the utterances of the characters and the author’s narration in Jacqueline Woodson’s Harbor Me. In analyzing the data, the writer used three concurrent processes. They are data reduction, data display, and conclusion drawing or verification. The result of this study found that irony and parody also as a theme in postmodernism literature. The irony and parody are used for illustrating the social condition in Harbor Me novel by Jacqueline Woodson. The characters experienced the irony as a real occurrence which is not accordance with their expectation. Meanwhile, they also experienced the parody for giving an insinuation by imitating others characters’ words and attitudes.  In addition, the presentation of irony and parody demonstrate the influence of theme in postmodernism. It is because the characteristics of irony and parody as the parts of postmodernism which have been stated by Lyotard in Sarup (1993). Keywords: Postmodernism, Irony, Parody